Signal processing in unmanned vehicles (ADAS) with MATLAB - Karpovich, B. О. (ХНУРЕ, 2025)
Advanced Driver Assistance Systems (ADAS) in unmanned vehicles rely on robust signal processing techniques to interpret sensor data and make critical navigation decisions. This paper examines key MATLAB implementations for ADAS applications.
Keywords: MATLAB; signal processing